Energy storage system modeling and control for power grid services - Zhou, Qidi (Nanyang Technological University, 2023)
The fast growth of energy demand, the incorporation of renewable energy sources, and the necessity to ensure a reliable and stable power supply have brought significant challenges to the existing load frequency control (LFC) systems. In the context of modern power networks, LFC systems are required to maintain the balance between generated and consumed power to guarantee stable frequency and secure operation of the interconnected grids. Incorporating energy storage systems (ESS) into LFC schemes has emerged as a promising solution to address these challenges, thereby improving the overall system performance. In this paper, we first introduce the principles and concepts of primary and secondary frequency control, and analyze their impacts on power system frequency stability. Then, we formulate models for the load frequency control system components. Subsequently, based on the energy storage system’s characteristics including the internal structure, equivalent circuit structure, and frequency regulation ability in LFC system, three common energy storage system models for LFC are investigated: Li-ion Battery Energy Storage System, Superconducting Magnetic Energy Storage System, and Redox Flow Battery. In particular, we established the Linear incremental models for these three batteries and developed corresponding simulation models in Simulink. Finally, load frequency control models using these three energy storage sources are established for a single-area control system and simulated in MATLAB/Simulink. We compare and analyze the frequency fluctuation with and without the connection of the battery models, as well as the settling time. The state-of-charge of the batteries is also compared.